Time-dependent seismic fragility and resilience assessment of a sea-crossing cable-stayed bridge under combined effects of corrosion and scour - Wu, Dianqi; Li, Zhong-Xian; Ding, Yang; Su, Junsheng (Engineering structures, 2025)
Sea-crossing bridges are inevitably subject to corrosion and scour effects over long-term service, resulting in significant time-dependent degradation of their seismic performance. Understanding the impacts of corrosion and scour on seismic fragility and resilience of such bridges is crucial for informed decision-making on their life-cycle operation and management. This paper investigates the time-dependent seismic fragility and resilience of a sea-crossing cable-stayed bridge considering the combined effects of corrosion and scour. The finite element time-varying model of the sea-crossing cable-stayed bridge under different service time is developed, incorporating the soil-pile interaction and considering the non-uniform corrosion under different exposure zones and the foundation scour. Three regular scour depths are selected for each service time to cover a wide range of degradation scenarios. The simultaneous three-directional seismic ground motions are then employed in the nonlinear time history analyses (NTHA) of the deteriorated bridge to capture the unfavorable responses. By incorporating corrosion degradation, the strain-based time-dependent capacity index is proposed and used to examine the seismic fragility of the studied bridge. Finally, the impacts of corrosion and scour on the lifetime resilience of the sea-crossing bridge is investigated. It is concluded that the seismic fragility of pylon increases over time, while scour exacerbates pile fragility but mitigates pylon damage to some extent. During the first 50 years, the bridge fragility is more affected by scour than corrosion, however, after that period, corrosion becomes the dominant factor affecting fragility. Corrosion and scour interact and mutually influence the seismic resilience of the bridge. In the absence of corrosion, the studied bridge exhibits higher resilience at a minor scour depth compared to the pristine state. This occurs because scour-induced pile damage helps to alleviate damage concentration in the pylon/pier zones, leading to a more balanced damage distribution and reducing overall damage to bridge system. However, the bridge resilience continues to decline with prolonged service period and increased scour depth. Additionally, increasing seismic intensity reduces bridge resilience and exacerbates the detrimental effects of corrosion on resilience loss. •Methodology for time-dependent seismic fragility and resilience assessment of sea-crossing bridge is presented.•Strain-based time-dependent damage evaluation index incorporating corrosion degradation is proposed.•Time-dependent degradation model of bridge considering non-uniform corrosion and soil-pile interactionsis developed.•Combined effects of corrosion and scour on seismic risk and resilience of sea-crossing bridge are investigated.